2009
DOI: 10.1590/s0100-736x2009000500015
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização fenotípica e molecular de amostras de Burkholderia mallei isoladas na Região Nordeste do Brasil

Abstract: Objetivou-se com este trabalho realizar o estudo bioquímico e molecular de amostras de Burkholderia mallei isoladas de eqüídeos com diagnóstico clínico e sorológico para o mormo e provenientes da Região Metropolitana do Recife-PE e Zona da Mata dos Estados de Alagoas e Pernambuco. Foram realizadas as técnicas microbiológicas para o isolamento e identificação fenotípica de B. mallei e as técnicas moleculares de ribotipagem-PCR e RAPD-PCR. Das oito amostras estudadas, quatro apresentaram pequenas variações fenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(18 reference statements)
0
5
0
3
Order By: Relevance
“…After confirmation of the disease in the country, there were some advances related to bacterial identification, including the use of a strain in the standardization of serological and intradermal diagnostic techniques. Silva et al [18] studied animals from Pernambuco and Alagoas and observed four groups of genotypes with distinct biochemical characteristics, indicating differences of the circulating strains in the study area. Subsequently, Girault et al [6] carried out the first draft of the genome of B. mallei strain 16-2438_BM#8 isolated from a mule in Pernambuco and concluded that a comparative genomic analysis of strains from different geographic regions and different hosts is necessary to improve the knowledge about this reemerging disease in the country.…”
mentioning
confidence: 99%
“…After confirmation of the disease in the country, there were some advances related to bacterial identification, including the use of a strain in the standardization of serological and intradermal diagnostic techniques. Silva et al [18] studied animals from Pernambuco and Alagoas and observed four groups of genotypes with distinct biochemical characteristics, indicating differences of the circulating strains in the study area. Subsequently, Girault et al [6] carried out the first draft of the genome of B. mallei strain 16-2438_BM#8 isolated from a mule in Pernambuco and concluded that a comparative genomic analysis of strains from different geographic regions and different hosts is necessary to improve the knowledge about this reemerging disease in the country.…”
mentioning
confidence: 99%
“…As bactérias identificadas apresentaram perfil fenotípico e genotípico que permitiu classificá-las como Burkholderia mallei, com características idênticas às observadas anteriormente por Yabuuchi et al (1992), Mota et al (2005), Silva et al (2008Silva et al ( , 2009.…”
Section: Resultsunclassified
“…Além disso, tendo em vista que espécies do gênero Burkholderia podem sofrer alterações em seu genótipo, principalmente quando se trata de cepas oriundas de regiões geográϐicas distintas (Silva et al 2009), acredita-se que um kit nacional produzido a partir de cepas nacionais possa reduzir signiϐicativa-mente os índices de resultados falso-positivos observados atualmente na FC.…”
Section: Resultsunclassified